Effect of intensified training on cognitive function, psychological state & performance in trained cyclists - Costello, S. E.; Rossiter, J. R. W.; Howatson, G.; Bell, P. G.; O´Neill, B. V.; van Someren, K.; Haskell-Ramsay, C. F. (European Journal of Sport Science, 2023)
Athletes often undertake intensified training loads prior to competition with the goal of functionally overreaching for temporary performance enhancement; however, little is known about the impact of this on cognitive function. The aim of this study was to investigate the effect of intensified training induced fatigue on cognitive function, psychological state and performance in trained cyclists. Twenty-three trained male cyclists were randomly assigned to an intensified training group or a control group for two-weeks, followed by a two-week taper period. At baseline, one-week, two-weeks and post-taper, participants undertook a series of cognitive, performance, mood and recovery-stress assessments. The training intervention significantly increased training volume, load and strain by 108%, 116% and 151% respectively. Peak and mean power output on a maximal test and time trial significantly decreased by 4.8% and 9.4% following the two-week training intervention compared to baseline, in addition to a 169% change in total mood disturbance and significant disruption to recovery-stress balance. No change in any cognitive measure was observed across the study period. Following a two-week taper, performance, mood and well-being measures returned to baseline. Two weeks of intensified training resulted in overreaching as identified by performance and psychological measures. Cognitive function was not sensitive to intensified training promoting caution with its use as a measure for the early identification of overreaching. Highlights